SOME FEATURES OF THE METHOD OF TEACHING AND TRAINING OF YOUNG BOXERS - Abdurakhmonov Shavkat; Bekmuratov Sodir (Journals Park Publishing, 2022)
Educational and sports work with adolescents should be considered as leading to active sports activities. The basis of the recruitment of groups should be age, physical development and, preferably, weight category. This is convenient, because it will be possible to choose exercises for all those involved in the group.